Vitellogenesis of basal trematode Aspidogaster limacoides(Aspidogastrea: Aspidogastridae) - Levron, Céline; Poddubnaya, Larisa; Oros, Mikuláš; Scholz, Tomáš (Parasitology international, 2010)
The vitellogenesis of the trematode Aspidogaster limacoides (Aspidogastrea: Aspidogastridae), a parasite of cyprinid fishes, is described here using transmission electron microscopy. Four different stages of vitellocytes are differentiated: immature vitellocytes, early maturing vitellocytes, advanced maturing vitellocytes and mature vitellocytes. The process follows the same general pattern already described in other free-living neoophorans and parasitic flatworms (i.e. Trematoda, Monogenea and Cestoda): differentiation into mature vitelline cells involves the development of mitochondria, granular endoplasmic reticulum, Golgi complexes, lipid droplets and shell-globules. Mature vitellocytes of A. limacoides are composed of numerous shell-globule clusters, few lipid droplets and glycogen granules. They differ from those of another aspidogastrean Rugogaster hydrolagi in that they possess numerous globules tightly packed and by the presence of only one type of vitelline material. The interstitial tissue of vitelline follicles of A. limacoides contains a peripheral nucleus and long cytoplasmic projections extending between vitelline cells. Since aspidogastreans are considered as an archaic group of parasitic flatworms and thus have a strategic phylogenetic position, future works needs to pay special attention to the ultrastructural and chemical composition of mature vitellocytes within this basal group of trematodes.
Keywords: Animals; ovum; Microscopy, Electron, Transmission; Cyprinidae; nemoci ryb; Trematoda; vitelogeneze; Female; transmisní elektronová mikroskopie; zvířata; Ovum; Fish Diseases; infekce červy třídy Trematoda; Vitellogenesis; Trematode Infections; ženské pohlaví